T* reatment of vulgar and plantar warts - A. N. Khlebnikova; Ye. V. Seleznyova; O. V. Dorokhina (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents data on clinical forms of warts associated with different types of human papillomavirus. The authors analyze the following wart treatment methods: excision, chemical and immune. Based on literature sources, the authors assess the efficacy, advantages and disadvantages of well-known treatment methods. The authors describe their own experience of treating primary and recurrent vulgar and plantar warts with an up-to-date chemical destruction drug - Mardil Zinc Max, a solution containing a complex compound of 1.5% zinc 2-chloropropionate in 2-chloropropionic acid. The efficacy of treatment of vulgar warts was 100%, and that of plantar ones - 62.5%. Clinical recovery was observed both in case of primary and recurrent processes. The treatment had no adverse effects or complications and was characterized by a low injury rate, good tolerance and full tissue recovery without any cosmetic defects.